Análise comparativa de características reprodutivas entre fêmeas de falcão-gerifalte (Falco rusticolus) e híbridas (Falco rusticolus e Falco cherrug) - Caroline Silva Vieira (2024)
Falconry is an ancient practice that involves the breeding and training of birds of prey for activities such as hunting, being an integral part of the culture in various regions, including the Middle East, Europe, and the Americas. Falconry is also valued for its applications in education, pest control, and preventing collisions with aircraft at airports. The most used species in this practice are the Gyrfalcon (Falco rusticolus), the Saker Falcon (Falco cherrug), and their hybrid descendants. Modern conservation efforts, such as the cryopreservation of germplasm and artificial breeding techniques, have played a crucial role in preserving these species. Hybridization offers advantages in selecting desired traits, although its impact on reproductive biology still requires further investigation. Seeking to fill some gaps in the knowledge about the reproductive biology of falcons, this study aimed to evaluate the ovaries of pure Gyrfalcon females (Falco rusticolus) and hybrid females (Falco rusticolus x Falco cherrug) with different degrees of hybridization, focusing on the quantity and diameter of follicles, as well as comparing the reproductive history between the groups. Ovaries were collected from 28 females, including 8 hybrid females 7/8 Gyrfalcon (Falco rusticolus (7/8) x Falco cherrug (1/8)); 10 hybrid females 6/8 Gyrfalcon (Falco rusticolus (6/8) x Falco cherrug (2/8)), and 9 pure Gyrfalcon females (Falco rusticolus), with ages ranging from 7 to 16 years. The collections were conducted in Morocco between late April and early May 2023, corresponding to the end of the breeding season for these birds in the region. Follicles were counted and classified as primordial, primary, pre-hierarchical, pre-ovulatory, post-ovulatory, and atretic. The analysis showed that age significantly impacts follicular morphology and reproductive capacity. With aging, there was a decrease in the number of primordial, primary, pre-ovulatory, and atretic follicles, suggesting a reduction in ovarian reserve and egg production. Pure females exhibited greater reproductive success in terms of eggs laid and viable offspring. Hybridization influenced follicle count, with 7/8 hybrids showing more pre-hierarchical and pre-ovulatory follicles. The diameter of follicles increased with age up to a certain point but decreased after 14 years. These results indicate that age and hybridization have complex effects on falcon reproduction, highlighting the need for further research on follicular development and reproductive efficiency in different degrees of hybridization.